Trends in Consultations for Schizophrenia and Non-affective Psychoses in Italian Emergency Departments During and After the 2020 COVID-19 Lockdown. Issue 1 (11th October 2021) - Balestrieri, Matteo; Rucci, Paola; Amendola, Davide; Bonizzoni, Miki; Cerveri, Giancarlo; Colli, Chiara; Da Re, Maria; Dragogna, Filippo; Ducci, Giuseppe; Elmo, Maria Giuseppa; Ghio, Lucio; Grasso, Federico; et al.
Abstract: Aims: To analyze the hospital emergency department (HED) consultations for schizophrenia-spectrum disorders in nine Italian hospitals during the 2020 lockdown and postlockdown periods, compared to the equivalent periods in 2019. Methods: Characteristics of consultations, patients, and drug prescriptions were analyzed. Joinpoint models were used to identify changes in the weekly trend of consultations. Results: During the 2020 lockdown the overall number of HED consultations for schizophrenia decreased by 40.7% and after the lockdown by 12.2% compared with 2019. No difference was found in the proportion of consultations that led to GHPU admissions or compulsory admissions. Suicidality rates did not differ across the two years, with the exception of ideations and plans (+5.9%) during the postlockdown period. We found an increase in benzodiazepine prescriptions in 2020 during the lockdown and postlockdown periods (+10.6% and +20.8%, respectively), and a decrease of prescriptions for short-acting sedative agents in the postlockdown period (–7.9%). An increase in the weekly trend of consultations occurred from March 11 to 17 (week 11) till June 26 to 30 (week 26). As a result, the initial gap in the number of consultations between the 2 years canceled out at the end of June. Conclusions: HED consultation rate for schizophrenia-spectrum disorders declined consistent with that of other psychiatric disorders. In the postlockdown period, the growth of suicidal ideation/planning and increase in the prescriptions of anxiolytic-sedating drugs may foreshadow that for some schizophrenia patients the exit from the lockdown period is not liberating, but rather a source of agitation or perturbation.